A Study on the Impact of Using Portfolio Assessment on English Reading Comprehension Ability of the First – Year English Major Students at Ha Nam Teachers’ Training College - Trần, Thị Phương Thảo (ĐHNN, 2017)
The purpose of this study was to investigate the effect of portfolio assessment on English reading comprehension ability of English major students at Ha Nam Teachers’ Training College. Participants consisted of 30 first year English major students. The portfolio assessment was integrated into classroom activities to explore to what extent the student’s English reading comprehension ability may be enhanced . Both quantitative and qualitative procedures were used for data collection and analysis. Data were obtained through four channels: a questionnaire with students, an interview with teacher, students’ portfolios and classroom observation. The results indicated that most of students and the teacher were in favour of portfolio assessment of reading and its procedures boosted students’ reading comprehension and raised their self – assessment and learner auto nomy as well . If portfolio assessment is planned carefully, it will become a powerful tool for assessing and enhancing students’ learning.